PENGARUH KOMPETENSI DAN TUGAS FUNGSIONAL TERHADAP KINERJA PENGAWAS PENDIDIKAN KABUPATEN WAJO - Alamsyah, Alamsyah; Syamsuri, Andi Sukri; Jam'an, Andi (COMPETITIVENESS, 2020)
Education supervisors based on the Decree of the Minister of State for The Utilization of State Apparatus No. 118/1996, are civil servants who are given full duties, responsibilities and authority by officials authorized to conduct supervision by carrying out assessments and coaching in terms of technical education and administration in pre-school, primary and secondary education units. This study aims to know and describe the influence of competence on the performance of education supervisors, knowing and describing the influence of functional tasks on the performance of education supervisors, knowing and describing the influence of competencies and functional tasks simultaneously on the performance of education supervisors in the Education Office of Wajo Regency. This research was conducted in May-June of 2019 at the District Education Office wajo with the object of this research is all education supervisors in the scope of the Wajo Kebupaten Education Office of 42 people. Respondents who were used by the population to give in this study were all education supervisors within the Wajo Kebupaten Education Office. The results of this study show that: 1) shows that competence has a significant positive effect on education supervisors; 2) demonstrate that functional tasks have a significant positive effect on education supervisors; and 3). Competencies and functional tasks together have a significant positive effect on the performance of education supervisors in the Education Office of Wajo Regency.Keywords: Competence, Functional Tasks, Performance, and Supervisory Education.